PENERAPAN METODE BLENDED LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA SISWA KELAS V DI SD NEGERI 3 SANUR: Metode Blended Learning, Pendidikan Agama Hindu dan Budi Pekerti - Kusuma Dhana, I Gusti Made; Sariani, Ni Putu Eka (JAPAM (Jurnal Pendidikan Agama), 2024)
The general objective of this research is to provide accurate and clear information to find out the application of the blended learning method, especially in Hindu religious and ethical education in learning at SD Negeri 3 Sanur and to gain clarity about the application of the blended learning method carried out during the Covid-19 period. This study specifically aims to explain the blended learning method in learning Hindu religious education and morals for fifth grade students at SD Negeri 3 Sanur, to explain the process of the blended learning method in learning Hindu religious education and morals for fifth grade students at SD Negeri 3 Sanur, to explain the implications of the blended learning method in learning Hindu religious education and ethics towards knowledge, attitudes, skills in fifth grade students at SD Negeri 3 Sanur. This research is classified as descriptive qualitative research. In collecting data, researchers used non-participant observation techniques, unstructured interview techniques, and document study techniques to obtain appropriate data at the research location. The results of the application of the blended learning method in learning Hindu religious education and morals in class V students at SD Negeri 3 Sanur can be viewed from aspects such as characteristic shape, study space, components of the blended learning method, then the process of the blended learning method consists of planning the blended learning method, the process of implementing the blended learning method,